The impact of technology level on global value chain formation - Tran Lam Anh Duong; Ivan Deseatnicov (FIW - Research Centre International Economics, 2019)
In this paper, we theoretically investigate the role of technology level in Global Value Chain (GVC) formation from two aspects: position and participation volume. We develop a simple two-country model where countries are heterogeneous with respect to their technology level and labor force. In GVC, there are a number of intermediate production stages with different technology thresholds. A country can produce at a stage if its technology level is higher than the stage's threshold. The unit labor requirement of a country in each stage is assumed to be inversely proportional to the difference between the technology level of the country and the technology threshold of the stage. According to this framework, the country with higher technology level will be producing at the stage with higher technology threshold. In contrast to previous studies that emphasize countries' position in GVC only, our work focuses on both the "position" and "volume" of participation. We find that GVC participation volume of a country, measured in terms of the number of production stages it holds, will increase if there is an increase in either the country's technology level or labor force.
Keywords: F12; F15; O33; 330; Global Value Chain; technology level; spider-like structure